THE IMPLEMENTATION OF PUBLIC HEALTH LAW IN STRENGTHENING HEALTH PROMOTION AND DISEASE PREVENTION - Muhamad Risal Tawil (JOURNAL OF LAW AND NATION, 2026)
Public health law plays an important role in regulating health efforts, promoting healthy behavior, and preventing diseases within modern health systems. This study aims to analyze the implementation of public health law to strengthen health promotion and disease prevention through a literature review. The research employs a qualitative method, drawing on library research to examine scholarly articles, academic publications, and international health reports on public health regulation and implementation practices. The findings indicate that effective public health regulations help control health risks, improve preventive health services, and encourage healthier public behavior. However, successful implementation depends on institutional capacity, law enforcement mechanisms, and community participation. In the era of global health challenges, adaptive regulatory frameworks and coordinated policy implementation are essential to strengthen health systems and ensure sustainable public health protection.